Intestinal microbiota and obesity - Zuziak, Patrycja; Ilnicka, Natalia; Abod, Leila; Matyja, Daria; Sadlik, Maria (Journal of Education, Health and Sport, 2022)
Introduction and purpose: The growing number of obese people is one of the greatest problems of modern medicine. It is estimated that every 10th person is obese. Recent studies also suggest that the gut microbiome may contribute to the pathogenesis of obesity. Description of the state of knowledge: Microbiota is named a super organ that has the ability to evolve in response to changing conditions within the host organism. It is named so because it is made up of over 100,000 billion cells that belong to different groups of organisms. Microbiota consists of bacteria, fungi, protists, viruses and archaea. This taxonomically diverse collective plays a vital role in maintaining the homeostasis of the human body. A well-balanced intestinal flora protects the digestive tract from colonization by pathogenic microorganisms, it is also important in maintaining the integrity of the intestinal walls, is involved in the synthesis of certain vitamins and plays a role in nourishing mucosa cells. Moreover, it is known that the microflora can influence body weight, insulin sensitivity, and metabolism of certain sugars and lipids. Disturbances in the composition of the microbiome (dysbiosis) lead to an increased absorption of short-chain fatty acids, which leads to an increase in endogenous YY peptide synthesis. This protein slows down the intestinal transit and indirectly leads to increased absorption of nutrients. This predisposes to the development of obesity. The use of prebiotics, probiotics and some antibiotics reduces intestinal dysbiosis. For obese patients, it is associated with reduction of insulin resistance and decrease in blood glucose level. Conclusions: In the light of the available studies, it can be concluded that intestinal dysbiosis may play a role in the pathogenesis of obesity. Unfortunately, the practical application of this knowledge is not yet well documented. Therefore this topic requires further experiments and analysis.